1986
DOI: 10.1159/000156263
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Social Referencing in Young Chimpanzees (Pan troglodytes)

Abstract: A captive chimpanzee group was observed in order to determine the extent to which the social interactions of the infants and juveniles (18–50 months) were affected by their mothers’ relationships with other adult group members. It was found that the young chimpanzees initiated more interactions with adults who interacted more with their mothers. A vast majority of those interactions occurred at significant distances from the mother. It is argued that these data imply a social-cognitive ability in young chimpan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 6 publications
0
17
0
2
Order By: Relevance
“…A previous study determined that the fa vorite adult interactants of these 6 infants were their mother's preferred social partners [7], In the current context another question concerning the favorite peer interactants of Overall preference rank of peer interactants as related to the preference rank of the offspring of the preferred adults (Spearman rank correlation coeffi cient r = 0.90; p < 0.05). BR = Brian; KP = Kipper; AN -Anja; GA ■ > Geor gia; RU = Rufus; ST -Storer.…”
Section: Maternal Social Relationsmentioning
confidence: 76%
See 2 more Smart Citations
“…A previous study determined that the fa vorite adult interactants of these 6 infants were their mother's preferred social partners [7], In the current context another question concerning the favorite peer interactants of Overall preference rank of peer interactants as related to the preference rank of the offspring of the preferred adults (Spearman rank correlation coeffi cient r = 0.90; p < 0.05). BR = Brian; KP = Kipper; AN -Anja; GA ■ > Geor gia; RU = Rufus; ST -Storer.…”
Section: Maternal Social Relationsmentioning
confidence: 76%
“…these infants could be asked: Are their favo rite peer interactants the offspring of their preferred adults and their mother's preferred social partners? Following the procedure of Evans and Tomasello [7], for each mother a preferred social partner ranking of the other 5 mothers was constructed from the scan samples. Infant preferences for adults were based on the relative frequency with which each infant initiated interactions with each of the 5 mothers other than its own.…”
Section: Maternal Social Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For nonhuman primates there is only one report providing evidence for social ref erencing in chimpanzees [18]. The authors observed a captive chimpanzee group in order to investigate the effect of the mother's relationship with other female adults on the interaction of her offspring with those adults.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed a captive chimpanzee group in order to investigate the effect of the mother's relationship with other female adults on the interaction of her offspring with those adults. According to Evans' and Tomasello's observations [18], infant chimpanzees' social interactions were affected by their moth ers' relationship with other adult group members. They concluded that infant and juve nile chimpanzees possess a social-cognitive ability to discern their mothers' relation ships with various individuals and to adjust their behavior accordingly.…”
Section: Introductionmentioning
confidence: 99%